Evaluation of the intensity of air transportation in the European region - Struk, Mikhail I.; Slivinskaya, Tatsiana V. (Journal of the Belarusian State University. Geography and Geology, 2017)
The goal of research is comparative assessment of the intensity of air transportation in the European region. To achieve this aim consistently solve issues on assessing the development of air transportation factors within it, their intensity applied to the passenger and cargo transportation in each country and their subsequent ranking on this indicator. The result was the estimation of factors that influence over the volume of air transportation in the European region, which showed their dependence on the geographical location of the countries and their population sizes and volume of the national economies. The quite dense network of airports and airlines which are varied in size, and the cost of transportation have been revealed, and almost absence of monopoly applied to the selected countries, which ensures competitive conditions in the airline industry, and creates favorable conditions for their development. The intensity of air transportation by country and carried out their ranking on this index, ref lected the degree of its dependence on the level of economic development level of the countries have been determined. The lowest degree is register mainly in the countries with economies in transition period, the highest – in the island countries (Ireland, Iceland), and in the most developed countries of continental Europe (Luxembourg, Norway). The territorial differences in the intensity of air transportation within the European region witch have been identified, allowed to divide it into 3 compact areas: East and South – mostly low, West and South-West – with moderate, Central and Northern – with its high degree.
Keywords: geography of transport; air transport; the European region; the intensity of air transportation; passenger transportation; cargo carriage; airport; airline; low-cost carrier